Perbedaan Persentase Suara Dengan Persentase Perolehan Kursi Legislatif Pada Pemilu 2009 di Kabupaten Tegal - Zimamul Khaq (Department of Political Science - Universitas Sains Al-Qur’an, 2018)
In converting the ballots achieved by political parties to legislative seats, the General Election Commission (KPU) in Indonesia uses different Voter Divider Numbers (BPP) in each electoral district. Determination of the amount of BPP is done by dividing the number of valid ballots for all political parties with the number of seats available in the electoral district in one region. Using the 2009 election case study in Tegal district, this study explained that the conversion model resulted in a large gap between the percentage of ballots achieved in the election and the percentage of seats gained in the legislature. This is due to the large number of party ballots lost in each electoral district in one region. Thus, there is a need for regulations that regulate the determination of the BPP which can minimize the ballots’ lost. Thus, the percentage of ballots obtained by political parties tends to be the same as the percentage of seats gained in the legislature.